Situations, presuppositions, and contexts - Lewerentz, LF (2021)
Definite descriptions (such as ‘the cat’) can often be used felicitously even when more than one object satisfies the overt descriptive material (such as ‘cat’). Situation semantics has been invoked to reconcile this observation with the idea that definite descriptions presuppose uniqueness. This thesis examines some of the challenges that this reconciliatory project faces. The focus is, in particular, on anaphoric uses that cross sentential boundaries and on the question of what role situations could play in modelling global and local conversational contexts as well as assertoric update.